Disminución de la fenolización de explantes in vitro de Plátano (Musa AAB) cv. Hartón Barraganete con diferentes antioxidantes en la etapa de inducción bajo condiciones de laboratorio - Solórzano Ponce, Julissa Melibeth (2024)
The present research work lies in improving the viability and development of explants, which is crucial for the efficient propagation of banana (Musa AAB) cv. Hartón Barraganete, increasing the production of healthy seedlings, reducing costs and improving crop quality. The main purpose of the research is to determine the decrease in phenolization of in vitro explants of Banana (Musa AAB) with different antioxidants in the induction stage under laboratory conditions. The study of the proposed variables is: to evaluate phenolyzation with different antioxidants, to establish the effect of these on the development of the explants, to identify the optimal concentration of each antioxidant and to analyze the survival rate of the centrifuged explants. The process to be evaluated consists of applying several antioxidants to the explants in different concentrations, monitoring their development and phenolization; and analyze the data to identify optimal conditions that minimize phenolization and maximize explant survival. The results of the study indicate that Ascorbic Acid (AA) is the most effective antioxidant for reducing phenolyzation in banana explants at all stages of the experiment, consistently maintaining the lowest phenol means throughout the nine days. In contrast, Activated Charcoal (AC) and absolute control with direct seeding (TA-SD) were shown to be the least effective treatments, with significantly higher phenolyzation levels. These findings suggest that the use of Ascorbic Acid as an antioxidant could be a viable strategy to minimize the negative effects of phenolization in banana in vitro cultures, which may improve success rates in micropropagation of this culture. However, the effectiveness of other antioxidants such as EDTA and T-AD, although better than that of CA and TA-SD, did not reach the levels of inhibition achieved by AA. Therefore, the implementation of Ascorbic Acid in banana micropropagation protocols is recommended, especially in the initial stages of cultivation.